How I experienced tele-intervention: Qualitative insights from persons who stutter - Raadhiyah Hoosain; Shabnam Abdoola; Esedra Krüger; Bhavani Pillay (South African Journal of Communication Disorders)
Background: Tele-intervention gained popularity, during the coronavirus disease 2019 (COVID-19) pandemic, prompting healthcare providers to adapt to remote service delivery. Research about stuttering treatment via tele-intervention in South Africa is limited. Speech-language therapists (SLTs) require further insights to deliver a well-supported approach for treatment of stuttering using tele-intervention, despite limitations such as technological disruptions, including loadshedding, that impact service reliability.